Experimental Study of Utilization Coconut Fiber as Additional Material and Slag as a Cement Substitution Against Compressive Strength and Split Tensile Strength of Concrete - Adlan Rafli Pramudya; Agung Sumarno (Neutron, 2022)
Development developments have an impact on the building materials industry sector. To reduce CO2 emissions due to soaring productivity of cement, the industry can use Ground Granulated Blast Furnace Slag (GGBFS) as a substitute for cement. This study aims to determine the effect of using GGBFS as a substitute for cement and coconut fiber as an additive on the workability, density, water absorption, compressive strength and split tensile strength of concrete at 3, 7, and 28 days. In this study using the experimental method with a total of 84 samples of cylindrical specimens with a size of 10cm x 20cm. This research was conducted with variations of GGBFS substitution of cement (0%, 35.5%, 43.5%) and coconut fiber as an additive (0.23%, 0.63%).The results of this study indicate that the optimum compressive strength test value at the age of 28 days is at GGBFS (35.5%) and coconut fiber (0.63%) reaches an average compressive strength of 32.32 Mpa. The SU1 variation (24.63 Mpa), SU2 variation (30.20 Mpa), SU3 variation (30.77 Mpa), SU5 variation (28.16 Mpa), SU6 variation (28.31 Mpa). Optimal splitting strength at the age of 28 days, namely the SU4 variation with GGBFS 35.5% and coconut fibers (0.63%) reached an average split tensile strength of 2.23 Mpa.